PENGARUH PANJANG SALURAN TRANSMISI TERHADAP TEGANGAN LEBIH TRANSIENT YANG DISEBABKAN KARENA PROSES ENERGIZED PADA SALURAN TRANSMISI 500 KV - Yuniarto, Yuniarto (Vocational School Diponegoro University, 2014)
Yuniarto, in this paper explain that the utility of high transmission line result in the transient over voltage in transmission-line will also increasingly higher, mainly for lightning and switching surge. Switching surge is a dominant factor to show up much transient over voltage in the transmission-line in the level of 230 kV or higher, if it is compared with lightning surge.Â Switching surge is caused by single energized process, the process itself to energize a transmission line in no load condition with energy power through switch closure operation. The research was aiming at observing the influence of transmission-line length to transient over voltage that occurred at the energized process in 500 kV transmission line Ungaran-Pedan, which used EMTP (Electromagnetic Transients Program) to simulate it.Â The result of simulation showed that the transient over voltage occurred along the transmission-line which caused the higher voltage increase, providing that the line is also longer. Key word : over voltage, Â transient, EMTP